Prediksi Harga Emas Dengan Menggunakan Metode Average-Based Fuzzy Time Series - Muhammad Riduan Indra Hariwijaya; Muhammad Tanzil Furqon; Candra Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Gold is a type of precious metal that has economic value and is often used for investmentl. Demand for gold increases from year to year, because many people already know that gold can be used as a safe haven. Safe haven is ownership in the form of investment assets that have a risk in low level, so that it becomes a protector of assets. Behind the benefits of gold, many investors discourage their investment because they are afraid of being cheated and cannot predict the increase or decrease in gold prices. Therefore we need a prediction of gold prices for investors to avoid losses when they want to invest in gold. One prediction method is Average-Based Fuzzy Time Series with the advantage to determine the interval effectively, the interval formed implements Average-based length so that it can increase the accuracy of the resulting prediction. The Average-Based Fuzzy Time Series implements fuzzy logic principles for the process of making predictions, such as fuzzy set, degree of membership, fuzzification, and defuzzification. The data used are daily gold prices taken from the official website of Logam Mulia with 2700 data with a time span from January 2010 to December 2019. The best error value MAPE obtained in the study was 0.34216% and included in the very criteria good because it's under 10%. Based on research conducted, the Average-Based Fuzzy Time Series method is good for predicting gold prices.